2019
DOI: 10.1159/000505739
|View full text |Cite
|
Sign up to set email alerts
|

Stereotactic Body Radiotherapy Combined with Transcatheter Arterial Chemoembolization versus Stereotactic Body Radiotherapy Alone as the First-Line Treatment for Unresectable Hepatocellular Carcinoma: A Meta-Analysis and Systematic Review

Abstract: Background: The superiority of stereotactic body radiotherapy (SBRT) combined with transcatheter arterial chemoembolization (TACE) compared to SBRT alone as the first-line therapy for unresectable hepatocellular carcinoma (HCC) remains unclear. We conducted this meta-analysis to compare the efficiency and safety of SBRT combined with TACE (ST group) and SBRT alone (SA group). Methods: We searched PubMed, Ovid Medline, Web of Science, Scopus, The Cochrane Library, ScienceDirect, EMBASE, Google Scholar, and CNKI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 27 publications
0
14
0
Order By: Relevance
“…Several recent studies documented that HCC patients receiving radiotherapy combined with other treatments had longer survival than those treated with radiotherapy alone [19][20][21]. A meta-analysis that compared the e cacy of TACE combined with radiotherapy with TACE alone treatment in patients with portal vein tumor thrombus (PVTT) demonstrated that the combined treatment yielded a higher objective response rate (ORR) and better survival bene ts than the TACE alone treatment [22].…”
Section: Discussionmentioning
confidence: 99%
“…Several recent studies documented that HCC patients receiving radiotherapy combined with other treatments had longer survival than those treated with radiotherapy alone [19][20][21]. A meta-analysis that compared the e cacy of TACE combined with radiotherapy with TACE alone treatment in patients with portal vein tumor thrombus (PVTT) demonstrated that the combined treatment yielded a higher objective response rate (ORR) and better survival bene ts than the TACE alone treatment [22].…”
Section: Discussionmentioning
confidence: 99%
“…TACE inhibits tumor growth by blocking tumor blood supply and creating hypoxia which induces tumor necrosis. A number of studies have shown that TACE can improve survival outcomes in patients with unresectable HCC [23][24][25]. Other studies have also demonstrated that patients with large HCC can benefit from preoperative TACE [26,27].…”
Section: Discussionmentioning
confidence: 99%
“…suggests higher response, local control, and survival rates with TACE and SBRT vs. SBRT alone. 78 Randomised studies comparing TACE with TACE and SBRT in unresectable HCC are ongoing ( NCT03895359 and NCT02794337 ).…”
Section: Evidence and Indications For Sbrt In Hccmentioning
confidence: 99%